2003
DOI: 10.1046/j.1432-1033.2003.03836.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Fetoprotein positively regulates cytochrome c‐mediated caspase activation and apoptosome complex formation

Abstract: Previous results have shown that the oncoembryonic marker a-fetoprotein (AFP) is able to induce apoptosis in tumor cells through activation of caspase 3, bypassing Fasdependent and tumor necrosis factor receptor-dependent signaling. In this study we further investigate the molecular interactions involved in the AFP-mediated signaling of apoptosis. We show that AFP treatment of tumor cells is accompanied by cytosolic translocation of mitochondrial cytochrome c. In a cell-free system, AFP mediates processing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…The presence of humoral factors modifying tumor growth in mouse serum was shown previously [2,7]. Our results are in line with previous data on the effects of hemoglobin degradation products and α-fetoprotein inducing apoptosis of tumor cells [6,11]. Presumably, one of the humoral factors, participating in tumor growth, is the complex of the studied proteins.…”
Section: Resultssupporting
confidence: 92%
“…The presence of humoral factors modifying tumor growth in mouse serum was shown previously [2,7]. Our results are in line with previous data on the effects of hemoglobin degradation products and α-fetoprotein inducing apoptosis of tumor cells [6,11]. Presumably, one of the humoral factors, participating in tumor growth, is the complex of the studied proteins.…”
Section: Resultssupporting
confidence: 92%
“…Hence, it should be feasible to detect remnants of both signal types on individual growth-regulating proteins such as AFP. The elegant studies by Dudich et al have revealed that AFP blocks apoptosis inhibition while promoting cell death effectors (caspases) in tumor and cell-free systems (Dudich et al, 2000;Semenkova et al, 2003;Dudich et al, 2006). On the basis of GenBank identification, an AA sequence resembling a Fas-like peptide stretch (AA #59-86) is readily detectable on domain I ( Figure 5E) of HAFP (39% identity; 23 AA in length).…”
Section: D) Oncogene Transcription and Expressionmentioning
confidence: 97%
“…Although AFP may not be the direct cause of the altered growth structures observed in birth defects, the belief is held that some shock/stress-induced conformational (variant) forms of this fetal protein may influence, modulate, or contribute to such events (Mizejewski, 2001a). Over the last two decades, reports have emerged that some of these HAFP forms can serve as dual regulators of growth, capable of either enhancement or inhibition of growth, in cancer as well as fetal cells (Mizejewski, 2002;Semenkova et al, 2003). Furthermore, AFP has been reported to promote growth via the protein kinase A pathway (Li et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…AFP is able to induce apoptosis in tumor cells (27,28). The molecular mechanisms are at least partly elucidated.…”
Section: Discussionmentioning
confidence: 99%